Novel mems biosensor with integmted impedance and mass-sensing capabilities - Nordin, Anis Nurashikin; Ibrahimy, Muhammad Ibn; Mel, Maizirwan; Voiculescu, Ioana (2011)
A BIOSENSOR DEVICE (1) PROVIDING AN ANALYSE PLATFORM FOR DETECNNG CELL GROWTH, COMPRISING OFAN ALUMINIUM NITRIDE (AIN) BASE (2), A SHEAR HORIZONTAL-SURFACE ACOUSTIC WAVE (SH-SAW) RESONATOR INCLUDING AN INPUT TMNSDUCER (4) AND AN OUTPUT TRA.NSDUCER (5) SYMMETRICALLY POSmONED ON THE ALUMTNUM NTTRIOE (ArN)BASE (2), A COUNTER ELECTRODE (6) POSMONED PAMLLEL TO WORKING ELECTRODES (7) ON THE ALUMINUM NITRIDE (ArN) BASE (2), FOR TMNSMTTTTNG FREQUENCY VOLTAGE TOWARDS THE WrNG CELL (3), A PLURAUTY OF WORKTNG ELECTRODES (7) POSMONED BENEATH THE LMNG CELL (3) ON THE ALUMINIUM NITRIDE (AIN) BASE (2) FOR RECEIVING FREQUENCY VOLTAGE FROM THE LMNG CELL (3), AN IMPEDANCE ANALYZER (8) FOR RECEMNG IMPEDANCE READINGS FROM THE COUNTER ELECTRODE (6) AND WORKING ELECTRODES (7), AND A BACK-ETCHED SIUCON SUBSTMTE (9) COUPLED TO THE ALUMINIUM NTTRIDE (AIN) BASE (2), FOR REDUCTNG C1JRRENT LOS' WHEREIN THE LMNG CErL (3) IS POSmONED rN BETWEEN OF THE INPUT TRANSDUCER AND OUTPUT TRANSDIrcER ON THE ALUMINIUM NITRIDE (AIN) BASE (4).